Elements associated with Iranian women\'s sexual behaviours: A cross-sectional study - Effat Merghati Khoei; Tahoora Alavi; Raziyeh Maasoumi; Fatemeh Sheikhan (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Women constitute about half of the Iranian population. Sexual behaviour is one of the most important elements in their lives. Identifying the elements associated with sexual behaviours seems necessary in order to draw a thorough picture of Iranian women's sexuality. Objective: To elicit information from Iranian women at their reproductive ages on sexual behaviours related to their elements including sexual capacity, sexual motivation, performance and sexual scripts. Materials and Methods: Study participants involved 295 women at reproductive age from five different cities. Women completed a national self-reporting questionnaire on elements related to sexual behaviours. The elements included sexual capacity, sexual motivation, sexual performance, and sexual script. Pearson’s correlation variance analysis and multi-linear regression were used to analyze data. Results: Significant positive correlation was found between the sexual capacity, motivation, performance, and sexual script (p<0.001). Linear regression showed that the effective variable on the sexual performance were women's ages (p=0.02), and tertiary education (p=0.05). A significant association was found between age and sexual motivation score, too. A significant relation was observed between the history of pregnancy and level of education with a positive response to sexual script questions. Conclusion: Identifying the elements of sexual behaviours would help women understand their sexual behaviours and related influencing factors. Therefore, enrichment of women's sexuality is needed; also a well-planned educational program is a need for women to understand their sexuality-related potentials.